The Relationship of Parental Attention to Learning Motivation of Elementary School Students - Yeni, Yeni; Triani, Susan Neni; Mertika, Mertika (Pedagogik Journal of Islamic Elementary School, 2023)
This study aims to accomplish three primary goals. Firstly, it seeks to clarify the connection between parental attention and students' motivation to learn. Secondly, it intends to outline the levels of learning motivation among fourth-grade students at SDN 90 Singkawang. Finally, it aims to establish the association between parental attention and the learning motivation of fourth-grade students at SDN 90 Singkawang. In this study, parental attention is considered the independent variable (X), while student learning motivation is regarded as the dependent variable (Y). The research methodology employed is descriptive, with a simple total sampling design. The participants included 25 students from the IV B class at SD Negeri 90 Singkawang. Data were gathered through questionnaires assessing parental attention and student learning motivation. Analysis was performed using the Pearson product-moment correlation technique, which revealed a significant correlation between parental attention and student learning motivation, with an observed correlation coefficient (r count) of 0.525 exceeding the critical value (r table) of 0.36. Thus, the hypothesis testing confirms a meaningful relationship between parental attention and student learning motivation.